An assessment of sleep quality in the elderly by using a modified scale - Varela Pinedo, Luis Fernando (2010)
Objective: To modify the currently used Sleep Hygiene Index by Mastin et al, in order to use it in the elderly. Material and method: An elderly-adapted version of the Sleep Hygiene Index originally proponed by Mastin et al. was translated, peer-validated and had its internal consistency assessed using Cronbachs Alpha method.   Results. The aforementioned instrument was translated and modifications for its use in the elderly were performed by six experts, and the instrument was validated for use in the elderly according to an 80% coincidence. A preliminary test for adjusting the scale was performed in 50 subjects who were more than sixty-years old, after signing an informed consent and excluding the illiterate persons, those with moderate or severe cognitive deterioration, and those with sever visual or auditory deficit. The modified instrument obtained a 0.7 value for reliability according to Cronbachs alpha test.   Conclusion: The modified Sleep Hygiene Index is a useful instrument to be applied in the elderly.